Help seeking for social anxiety: A pilot randomised controlled trial. (June 2017) - Griffiths, Kathleen M; Walker, Jennie; Batterham, Philip J
Objective: Although social anxiety disorder is a persistent and debilitating condition, only a minority of people with social anxiety disorder seek help and little is known about methods for promoting help seeking for social anxiety disorder. This pilot trial explored the potential effectiveness of an online program designed to increase help-seeking intentions for social anxiety disorder. Methods: Australian adults with symptoms of untreated social anxiety disorder were recruited online and randomised to either the Shyness Information Online intervention ( n  = 41) or an online attention control condition ( n  = 41). Each program together with a baseline and postintervention survey was delivered in one session. The primary outcome was intentions to seek help from a professional. Secondary measures included anxiety literacy, help-seeking attitudes, internalised stigma, and perceived need for treatment. The acceptability of the program content and feasibility of the recruitment method were also examined. Results: Although they did not demonstrate a significantly greater increase in help-seeking intentions relative to the control group ( p  = 0.097), those receiving the intervention showed more favourable attitudes towards seeking psychological help (Hedges' g  = 0.38; p  = 0.025) and a higher level of perceived need for treatment ( p  ≤ 0.001). Participants also showed a greater knowledge about social anxiety disorder at post-intervention than the control participants (adjusted Hedges' g  = 0.46, p  < 0.001). Most respondents were satisfied with the intervention content; the recruitment strategy appeared feasible. Conclusions: Further investigation of the intervention is warranted to test its effectiveness, explore the relationships between factors that influence social anxiety disorder help-seeking behaviour and to further test the validity of the social anxiety disorder help-seeking model on which the intervention was based.